The Upper Guinea Coast in Global Perspective - Knörr, Jacqueline; Kohl, Christoph (Berghahn Books)
For centuries, Africa s Upper Guinea Coast region has been the site of regional and global interactions, with societies from different parts of the African continent and beyond engaging in economic trade, cultural exchange, and various forms of conflict. This book provides a wide-ranging look at how such encounters have continued into the present day, identifying the disruptions and continuities in religion, language, economics, and various other social phenomena that have resulted. These accounts show a region that, while still grappling with the legacies of colonialism and the slave trade, is both shaped by and an important actor within ever-denser global networks, exhibiting consistent transformation and creative adaptation.
English
Keywords: Anthropology; Anthropology; Cape Verde; Creole language; Jola people; Rice; Sierra Leone